Thermographic ranges of dromedary camels during physical exercise: applications for physical health/welfare monitoring and phenotypic selection - Iglesias Pastrana, Carlos; Navas González, Francisco Javier; Ciani, Elena; Marín Navas, Carmen; Delgado Bermejo, Juan Vicente (Frontiers in Veterinary Science, 2023)
Despite the relatively wide knowledge ofn camel biomechanics, the immediate functional response that accompanies the execution of physical exercise remains unapproached. Hence, selective breeding programs are lacking from empirical basis to reach genetic improvement for physical stress tolerance traits and monitor camel welfare in this regard. Therefore, selective breeding programs lack an empirical basis to achieve genetic improvement of physical stress tolerance traits and monitor camel welfare in this regard. Given the fact that physical exercise increases net heat production, infrared thermography (IRT) was selected to study the temperature changes at the skin surface of the different body areas in clinically normal dromedary camels mostly relegated to leisure activities. Such thermophysiological responses can be used as indirect measures of tissue activity in response to exercise, hence reliable indicators of animal tolerance to physical exercise-induced stress. Specifically, a lower dispersion at the individual level of the surface temperature at the withersscapular cartilage region, shoulder joint, and rump pelvis regionareas, as well as lower values for Tmax and Tmin at the region of the corneaocular region, pectoral muscles, semimembranosus-semitendinosus muscles and hind fetlock after exercise, have to be remarked as breeding criteria for candidate selection. Sex, castration, age and iris pigmentation did also significantly impact thermo-physiological response to exercise in the study sample, which can be attributed to hormones, general vigor and visual acuity-mediated effects. 1 Con formato: Inglés (Estados Unidos) Con formato: Inglés (Estados Unidos) Con formato: Inglés (Estados Unidos)